2020
DOI: 10.3390/antiox9121283
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetyl Cysteine Targets Hepatic Lipid Accumulation to Curb Oxidative Stress and Inflammation in NAFLD: A Comprehensive Analysis of the Literature

Abstract: Impaired adipose tissue function and insulin resistance remain instrumental in promoting hepatic lipid accumulation in conditions of metabolic syndrome. In fact, enhanced lipid accumulation together with oxidative stress and an abnormal inflammatory response underpin the development and severity of non-alcoholic fatty liver disease (NAFLD). There are currently no specific protective drugs against NAFLD, and effective interventions involving regular exercise and healthy diets have proved difficult to achieve an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 80 publications
1
25
0
Order By: Relevance
“…However, in our study, NAC overdose (N800) induced liver steatosis and dramatically increased hepatic TG levels at 48 h post-NAC injection. On the other hand, NAC has been reported to block hepatic lipid accumulation in preclinical models of NAFLD [ 51 ]. In rodent disease models, NAC neutralizes oxidative stress by providing GSH, thereby reducing the development of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, NAC overdose (N800) induced liver steatosis and dramatically increased hepatic TG levels at 48 h post-NAC injection. On the other hand, NAC has been reported to block hepatic lipid accumulation in preclinical models of NAFLD [ 51 ]. In rodent disease models, NAC neutralizes oxidative stress by providing GSH, thereby reducing the development of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) can manifest as simple steatosis or progress to chronic liver damage, due to the increased hepatic flow of free fatty acids, which generates an increase in oxidative stress concomitant with the suppression of intracellular antioxidant activity. Evidence from experimental studies has revealed that NAC blocks the accumulation of liver lipids and reduces proinflammatory markers, such as IL-6 and IL-1β, TNF-α, and NF-κB [ 159 ].…”
Section: Clinical Indicationsmentioning
confidence: 99%
“…There is evidence that NAC may block hepatic lipid accumulation and provide therapeutic benefit against metabolic complications found in nonalcoholic fatty liver disease (NAFLD). This is primarily due to the antioxidant effects and attenuation of lipid peroxidation [ 64 ]. This is supported by most preclinical studies and a few clinical studies, and there is an urgent need for larger clinical studies.…”
Section: Metabolic Syndrome Including Nonalcoholic Fatty Liver Disease Diabetes and Polycystic Ovarymentioning
confidence: 99%